Design of a Light Intensity Regulator with Remote Control for Incandescent Lamps - Akhmad Yani (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2022)
Research has been carried out on the design of a light intensity regulator with a remote control on incandescent lamps. This study aims to design and manufacture a light intensity controller that can be controlled remotely. This research uses Infrared Light Emitting Diode (LED) as transmitter and phototransistor module as receiver. The results of this study indicate that the tool that has been successfully designed and made can function up to a distance of 300 cm.